2018
DOI: 10.1038/s41467-018-07047-7
|View full text |Cite
|
Sign up to set email alerts
|

Controlling reaction pathways of selective C–O bond cleavage of glycerol

Abstract: The selective hydrodeoxygenation (HDO) reaction is desirable to convert glycerol into various value-added products by breaking different numbers of C–O bonds while maintaining C–C bonds. Here we combine experimental and density functional theory (DFT) results to reveal that the Cu modifier can significantly reduce the oxophilicity of the molybdenum carbide (Mo2C) surface and change the product distribution. The Mo2C surface is active for breaking all C–O bonds to produce propylene. As the Cu coverage increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(118 citation statements)
references
References 49 publications
8
108
0
Order By: Relevance
“…In contrast, on the Mo 2 C surface, the intensity of the ν (CO) mode was reduced, confirming the C−O bond cleavage and being consistent with the lower onset temperature of the propylene desorption from the fresh Mo 2 C surface than on Fe/Mo 2 C (Figure (b)). On Cu/Mo 2 C, the decrease of the v(CO) mode intensity was consistent with the formation of C−O bond scission products and the desorption of acetol, as reported previously . In summary, the HREELS results indicated that Mo 2 C interacted with the oxygen in glycerol more strongly than Fe/Mo 2 C and Cu/Mo 2 C, and Pt/Mo 2 C showed reforming activity.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, on the Mo 2 C surface, the intensity of the ν (CO) mode was reduced, confirming the C−O bond cleavage and being consistent with the lower onset temperature of the propylene desorption from the fresh Mo 2 C surface than on Fe/Mo 2 C (Figure (b)). On Cu/Mo 2 C, the decrease of the v(CO) mode intensity was consistent with the formation of C−O bond scission products and the desorption of acetol, as reported previously . In summary, the HREELS results indicated that Mo 2 C interacted with the oxygen in glycerol more strongly than Fe/Mo 2 C and Cu/Mo 2 C, and Pt/Mo 2 C showed reforming activity.…”
Section: Resultssupporting
confidence: 90%
“…With the addition of Pt modifier on Mo 2 C, the reaction pathway of glycerol changed from HDO to reforming. On Cu/Mo 2 C, glycerol only underwent one C−O bond scission to form acetol (Figure (d)), likely due to the lower oxophilicity of the Cu modifier. Comparing the reaction pathways on these four surfaces (Scheme ), Mo 2 C and Fe/Mo 2 C were able to cleave all the C−O bonds in glycerol to produce propylene, Cu/Mo 2 C broke only one C−O bond of glycerol to form acetol, while Pt/Mo 2 C favored the C−C and C−H bond scissions to produce CO and H 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations